Effectiveness of brief mindfulness intervention in reducing psychological distress among family caregivers of cancer patients - Anak Agung Sri Sanjiwani; Ketut Lisnawati (Empathy : Jurnal Fakultas Psikologi, 2025)
Family caregivers are particularly vulnerable to psychological distress due to the cumulative burden of caregiving responsibilities and the challenges of balancing their own personal needs. Mindfulness-based approaches have been widely recognized as promising strategies for alleviating psychological distress. This study aimed to examine the effectiveness of a Brief Mindfulness Intervention (BMI) in reducing psychological distress among family caregivers of breast cancer patients. A quasi-experimental design was employed, and purposive sampling was used to recruit 30 family caregivers (15 in the intervention group and 15 in the control group). The intervention consisted of a single 90-minute session, and psychological distress was assessed using the DASS-21. The findings indicated significant reductions in depressive symptoms, anxiety, and stress following the BMI (depression: p = 0.002; anxiety: p = 0.000; stress: p = 0.000). Cohen’s d effect size demonstrated that BMI produced substantial effects, particularly on anxiety and stress (depression: d = 0.43338; anxiety: d = 1.6170; stress: d = 1.1240). These results suggest that BMI may serve as a feasible and preliminary coping strategy for mitigating psychological distress among family caregivers facing emotionally demanding caregiving situations.